Anaplastic large cell lymphoma with TP63 rearrangement: A dismal prognosis. Issue 3 (5th February 2019) - Yamashita, Takahisa; Higashi, Morihiro; Kawano, Ryutaro; Momose, Shuji; Tokuhira, Michihide; Kizaki, Masahiro; Tamaru, Jun‐ichi
Abstract : Anaplastic large cell lymphoma (ALCL) with TP63 rearrangement is a new entity and has the most dismal prognosis in all types of ALCL. This might be due to the resulting fusion protein having N‐terminal truncated p63 with high oncogenic ability. Since this N‐terminal domain has the function of tumor suppressor activity, the mechanism for high oncogenic capacity is thought to be the dominant negative function. Here, we report two ALCL cases with TP63 rearrangement that was each given too short a prognosis (Case 1 and 2: four and six months) in spite of intensive treatment. Immunohistochemically, p63 was highly expressed, and a sprit signal was detected using a TP63 break apart fluorescence in situ hybridization (FISH) in each case. Additionally, a poor prognostic marker of ALCL, all cytotoxic molecules (TIA‐1, Granzyme B, and Perforin) were also expressed in almost all ALCL cells. Taken together, we suggest that not only the dominant negative function of N‐truncated p63 but also the effect of cytotoxic molecules may influence the dismal prognosis of ALCL with TP63 rearrangement.